Effectiveness of constructed farm wetlands in attenuating faecal indicator fluxes to watercourses from yard runoff on livestock farms. (6th March 2021) - Kay, David; Clarke, Aldwyn; Crowther, John; Davies, Cheryl; Francis, Carol A.; Stapleton, Carl M.; Watkins, John; Wyer, Mark D.
Abstract: Constructed farms wetlands (CFWs) are increasingly being used to treat faecally contaminated 'dirty waters' from yard areas on livestock farms. The findings of the present study, undertaken at the Pwllpeiran experimental CFW, West Wales, provide empirical data on the effectiveness of CFWs in attenuating faecal indicator organism (FIO) concentrations and fluxes to the receiving waters to which they discharge; and insight into the extent to which attenuation rates are affected by retention times within the CFW and seasonal factors. Based on the maximum flows that a CFW is being designed to treat, an equation is developed to enable estimates to be made of the size of wetland required to achieve a desired level of FIO attenuation. Other aspects of CFW design to optimise FIO attenuation are considered, including the construction of frequent baffles (transverse ridges), leaving parts of cells unvegetated and incorporating an initial settling pond.